A study comparing the biologic drugs ixekizumab and guselkumab for the treatment of moderate‐to‐severe plaque psoriasis. (1st June 2020) - Blauvelt, A.; Papp, K.; Gottlieb, A.; Jarell, A.; Reich, K.; Maari, C.; Gordon, K.B.; Ferris, L.K.; Langley, R.G.; Tada, Y.; Lima, R.G.; Elmaraghy, H.; et al.
Summary: Psoriasis is a skin disease that causes red, scaly and itchy patches of skin all over the body. It affects about 125 million people worldwide. As well as causing decreased quality of life, more widespread psoriasis often affects internal health. New drugs developed in the last few years often help people with psoriasis to achieve completely clear skin, and improve overall health. Two of these drugs are ixekizumab (IXE) and guselkumab (GUS). IXE and GUS work in different ways, however, and some prior research showed that IXE may work faster than GUS. In this study, researchers from the U.S.A. and Canada tested these drugs head‐to‐head, measuring speed of clearance and complete skin clearance rates over the first 12 weeks after starting drug. People in this study received either IXE or GUS. After 12 weeks, completely clear skin was achieved by 16% more people if they were treated with IXE compared to GUS (41% of people who took IXE versus 25% of people who took GUS). More people on IXE than GUS had 50% clearer skin after just one week and 75% clearer skin after two weeks. Itching, skin pain, and quality of life also improved faster with IXE compared to GUS. The number of patients with serious side effects was similar for IXE and GUS. Overall, people with psoriasis who take IXE may get clear skin faster and feel better more quickly than people who take GUS. This is a summary of the study: A head‐to‐head comparison of ixekizumab vs. guselkumab in patients with moderate‐to‐severe plaque psoriasis: 12‐week efficacy, safety and speed of response from a randomized, double‐blinded trial